The Effectiveness of Communicative Games in Developing Speaking Skills of Form One Students in SMKA Maahad Hamidiah, Kajang - Abd. Rahim, Normaliza (1998)
This study aims to (1) investigate the Form One speaking skill through communicative game (2) provide variety in classroom teaching and make learning useful and meaningful in context and (3) determine the teachers and student perception on communicative games. The teacher-related variables are mere demographic characteristics (i.e. gender, teaching experience and in-service courses attended) and the teachers' experience in using communicative games. The student-related variables are mere demographic characteristics (i.e. gender, age, parent's occupation and their grades in the mid semester examination) and the students' experience in learning through communicative games 95% of the respondents in SMKA Maahad Hamidiah agree that communicative games are the most effective way in developing speaking skill.